RISIKO TINGKAT KEMATIAN AYAM BROILER PADA PETERNAKAN PT. TUNAS SATWA MANDIRI - Dewi, Ilma Satriana (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
PT. Tunas Satwa Mandiri is a livestock company that cultivates broiler chickens. However, its business activities indicate a high level of mortality risk. This study aims to analyze: Sources of risk of broiler chicken mortality, The possibility of risk (probability), The impact of losses from the risk of broiler chicken mortality, and Strategies for handling the risk of broiler chicken mortality on the PT. Tunas Satwa Mandiri farm. The research method is a case study on the broiler chicken farming business of PT. Tunas Satwa Mandiri. The sampling method in this study uses a census method consisting of 1 farm manager and 13 employees. The data analysis used is descriptive analysis, z-score, and Value at Risk (VaR). The results of the study show: There are four sources of production risk, namely retired broiler chickens, weather conditions, disease attacks, and predator attacks. The greatest possibility of risk (probability) is disease attacks with a value of 42.07 percent and the smallest probability is predator attacks with a value of 15.62 percent. The impact of the risk that causes the greatest loss is disease attacks amounting to Rp. 55,720,792, while the smallest loss impact is predator attacks amounting to Rp. 26,058,553. Risk management strategies in broiler chicken farms of PT. Tunas Satwa Mandiri based on risk mapping are preventive strategies and mitigation strategies.